Purity Algorithm in Determining System of The Productivity of Rice Harvesting Areas in Kabupaten Aceh Utara - Novia Hasdyna; Sujacka Retno (Universitas Medan Area, 2022)
Purity is an algorithm thatcan be used to measure the purity value of the data. This research aims to implement the purity algorithm to provide the information on the area of rice harvest productivity in Kabupaten Aceh Utara. The highest purity value indicates the highest harvest productivity area. With lower Purity value indicates lower harvest productivity areas. The data used in this research obtained from the Dinas Pertanian dan Pangan Kabupaten Aceh Utara in 2015-2019, which consists of 26 sub-districts. The results of this research indicate that the areas that are very productive in producing rice in Aceh Utara are based on planting area (ha), harvested area (ha), productivity (kw/ha), production (ton), and production presentation using Purity. In 2015, the highest purity value was in Muara Batu sub-district with a value of 0.742189869. In 2016, the highest purity value was in Sawang sub-district with a value of 0.732474998. In 2017, the highest purity value was in Sawang sub-district with a value of 0.732862423. In 2018, the highest purity value was in Muara Batu sub-district with a value of 0.742319507. In 2019, the highest purity value was in Tanah Luas sub-district of 0.735502499. The system created on web using the PHP programming language.